2017
DOI: 10.1016/j.eja.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Co-learning cycles to support the design of innovative farm systems in southern Mali

Abstract: Farm systems were re-designed together with farmers during three years (2013–2015) in Southern Mali with the aim to improve income without compromising food self-sufficiency. A cyclical learning model with three steps was used: Step 1 was the co-design of a set of crop/livestock technical options, Step 2 the on-farm testing and appraisal of these options and Step 3 a participatory ex-ante analysis of re-designed farm systems incorporating the tested options. Two iterations of the cycle were performed, in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…This change was based on findings of a series of co-learning cycles involving farmers of the four farm types (HRE-LH, HRE, MRE and LRE) during three years of research in the study area. The co-learning cycles were composed of (i) on-farm testing of intercropping and stall-feeding options by about hundred farmers in nine villages of the Koutiala region, (ii) appraisal of options by farmers, and (iii) farm system re-designs and ex-ante analysis assessed by farmers (Falconnier et al, , 2017. The co-learning process indicated that maize-cowpea intercropping is a low-risk, profitable option, which can be combined with stall feeding of lactating cows for increased milk production without compromising food self-sufficiency of the household.…”
Section: Narrowing Yield Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…This change was based on findings of a series of co-learning cycles involving farmers of the four farm types (HRE-LH, HRE, MRE and LRE) during three years of research in the study area. The co-learning cycles were composed of (i) on-farm testing of intercropping and stall-feeding options by about hundred farmers in nine villages of the Koutiala region, (ii) appraisal of options by farmers, and (iii) farm system re-designs and ex-ante analysis assessed by farmers (Falconnier et al, , 2017. The co-learning process indicated that maize-cowpea intercropping is a low-risk, profitable option, which can be combined with stall feeding of lactating cows for increased milk production without compromising food self-sufficiency of the household.…”
Section: Narrowing Yield Gapmentioning
confidence: 99%
“…S1) so that no labour shortage had to be expected. Falconnier et al (2017) showed that with actual household size and cropland area, there is no human labour shortage for cropping activities; the shortage is rather in the availability of oxen. If higher out-migration rates had to be considered in other studies, leading to lower number of people compared with the baseline, an effect of labour loss on yield could be introduced in the modelling framework.…”
Section: Change In Food Self-sufficiency and Income Differed Per Farmmentioning
confidence: 99%
“…Most previous studies applied the DEED cycle once (Tittonell et al, 2009;Rufino et al, 2011;Franke et al, 2014). However, an iterative application of this cycle allows farmers to test the options, provide feedback on them and to be engaged in the re-design of options (Dogliotti et al, 2014;Falconnier et al, 2017). Moreover, following up on farmers who (dis)continue using options provides insight in the actual relevance of options for different types of farmers, as well as farmers' own adaptations to the options that could further inform the re-design of technologies.…”
Section: Co-designing a Relevant Basket Of Options For Legume Cultivamentioning
confidence: 99%
“…The re-design of the technologies in the demonstrations each season allowed taking into account treatments that farmers valued, but at the same time this meant that treatments could not always be compared over multiple seasons. This presented a trade-off between reflexive design on the one hand (Mierlo et al, 2010;Falconnier et al, 2017), and agronomic research requirements on the other. However, even those treatments that could be compared over multiple seasons showed a large variation in yield (in line with earlier findings on farmers' fields of Franke et al, 2016;.…”
Section: Lessons Learned From Developing and Applying A Co-design Promentioning
confidence: 99%
See 1 more Smart Citation